GLOBAL TRENDS IN NEW ECONOMY AND CHANGES IN MARKETING, TOURISM AND MANAGEMENT (International Journal of Innovative Technologies in Economy, 2022)
In the second half of the 20th century and the beginning of the 21st century, significant changes occurred in the world, which altered not only the common space of economic systems, but also the direction of the subject fields. Some of them are service-related, specifically, field computerization, management and marketing activities. Foreign experts refer to this transformation as the "service revolution." The terms of the transformation of the modern economy and globalization create interesting situations in the theory and practice of economic and organizational-management disciplines. Marketing is considered in the field of economics. As noted by scientists, marketing in different fields has undergone a sharp transformation. At the same time, in management development a new paradigm was expressed, so called service-management. Service-management aims at creating broad systemic viewpoints, explaining and debating intriguing issues on individual situations that occur in quasi-service systems; Also, developing new methods and approaches of utilizing today’s environment and its potential in a more systematic manner. In fact, marketing researchers became interested in studying the specific problems for the first time, in the 1970s of the 20th century. Precisely during this time, the first PhD theses, articles, and research were completed. They discussed actual issues that practically affected every sector of business. Mainly the topics were devoted to marketing and related activities and related fields.